Median circular in statistical analysis angular data - Куц, Ю.В.; Монченко, О.В. (Proceedings of National Aviation University (archive), 2006)
Definition a round mediane in statistic processing of the random angles is offered. The realization of the offered technique is considered on an example of the use model in MatLab.